Breaking Bad, Making Good: Notes on a Televisual Tourist Industry. (14th March 2016) - Tzanelli, Rodanthi; Yar, Majid
Abstract: This article explores emerging intersections between the consumption of mediated popular culture and the real and imagined topographies within which those representations are framed. Through an examination of the 'televisual tourism' centred around the successful TV series Breaking Bad, we scrutinise the multiple modes of sensorial and embodied travel experience enjoyed by fans of the show as they consume their way around the show's sites, scenes and tastes in the city of Albuquerque. This exploitation of media textuality through fan tourism is, we suggest, centred upon a carefully managed commodification of crime, criminality and transgression.